Relationship between Consumption of Foods Rich in Omega-3 Fatty Acids and Dysmenorrhea in Students of SMAN 1 Gondangrejo Karanganyar - Arini Hidayati; Kusmadewi Eka Damayanti; Arsita Eka Prasetyawati (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: Prevalence of dysmenorrhea in SMAN 1 Gondangrejo Karanganyar is 88%. One cause of dysmenorrhea is due to elevated levels of prostaglandin because lower consumption of omega-3 fatty acids. This study aims to know the relationship between consumption of foods rich in omega-3 fatty acids and the incidence of dysmenorrhea among the students of SMAN 1 Gondangrejo Karanganyar. Methods: This study was an analytical observational study with cross-sectional approach. 125 subjects of this study were chosen by simple random sampling from students in SMAN 1 Gondangrejo Karanganyar. Each subject was measured consumption of omega-3 with Semiquantitative Food Frequency Questionnaire (SQFFQ) consumption omega-3 fatty acids and dysmenorrhea with questionnaire modified from Menstrual Symptom Questionnaire (MSQ). The data of this study then analyzed by using chi-square test to determine the relationship between consumption of foods rich in omega-3 fatty acids and dysmenorrhea. Results: 125 students were observed and obtained 79,2% of them consume adequate amounts of omega-3 fatty acids (?1.1 g/day) and 28% experienced dysmenorrhea. The results of data analysis using chi-square test was obtained p = 0.001 that shows there is a significant or meaningful relationship between consumption of foods rich in omega-3 fatty acids and dysmenorrhea. Conclusions: There is a significant relationship between omega-3 fatty acids and dysmenorrhea. Keywords: Omega-3 fatty acids, Dysmenorrhea.